Pemanfaatan Teknologi dalam Evaluasi Pembelajaran Tingkat Sekolah Dasar - A’la, Nadia Ibadatul; Bilqist, Philien Sophia Ikrima; Anisa, Tria Noer; Aini, Vika Zahra (Al-DYAS, 2023)
Evaluation is a very important component in learning activities and it is something that should not be missed. With the learning evaluation, both educators and students are able to find out the extent to which students' abilities and understanding of a learning material. The application of technology for learning evaluation is the practice and theory in the design, development, utilization, management and evaluation of processes and resources for learning. The use of technology in learning evaluation activities makes it easier for educators to process and measure students' abilities towards a learning material. The research method used in this article is descriptive research which will involve collecting qualitative data from various sources, such as questionnaires, observations, interviews, and document analysis. With several applications as an evaluation tool it can also be used to create questionnaires, send surveys, create quizzes for students and collect information in a fast, easy and efficient way.